Re-architecture for requirements of academic space development in the universities: design and validitation of RASD questionnaire - Zahra Karimian; Mahmoud Abolghasemi (Scientific Reports)
Abstract Universities are the cornerstone of social development and progress; however, it is essential to enhance the academic environment to support this mission. The objective of this research is to identify the Requirements for Academic Space Development (RASD) in universities. The present study was conducted in 2022–2023 using a mixed-method with a qualitative-quantitative sequence. The qualitative section was conducted using purposive sampling and semi-structured interviews with 20 experts of Iranian universities. The data were analyzed using content and thematic analysis at three levels of codes (Items), components, and themes (Main concepts), and then, it was examined quantitatively using a survey on 265 faculty members. For data analysis and validate the instrument, the face and content validity (CVI/CVR), reliability and construct validity were examined. Exploratory and confirmatory factor analysis were used to validate the questionnaire using SPSS 24 and Liseral 8.5 software. In qualitative stage, 67 codes, 4 concepts (formal, political, cultural, and scientific), and 14 components were extracted, which resulted in the word “Re-architecture” based on the acronym of the first letter. The content validity of the RASD questionnaire was confirmed with CVI = 0.941 and CVR = 0.940. The overall reliability was 0.962. For construct validity, first, the sample adequacy was confirmed with KMO = 0.928 and the Bartlett test (P < 0.001). In general, the quantitative section also extracted 14 factors that estimated 70.229% of the total variance. The “Happiness” had the highest factor loading (30.35%), followed by “Unity” (6.11%), “Thinking” (4.23%), Refining” (3.87%), “Expediency” (3.22%), and “Interaction” (2.83%) with the highest factor loadings. Universities need a rethinking, a concept that has been addressed in this research as “Re-architecture”. Perhaps the choice of this term is appropriate because we also need changes in universities, by combining science, re-engineering, cultural considerations, and an artistic integration of all factors influencing academic development.